Reproductive Performance of Buffalo (Bubalus bubalis) in Small Scale Farm in Boyolali Regency Central Java - Zahrotul Fitriani; Joko Riyanto; Ratih Dewanti; Muhammad Cahyadi; Ari Kusuma Wati; Wari Pawestri; Yanti, Yuli (Jurnal Ilmu-Ilmu Peternakan, 2023)
This study aimed to determine the reproductive performance of female buffalo in Boyolali Regency, Central Java, Indonesia. The sampling method used was the purposive sampling method. The number of respondents was 30 buffalo farmers with a total sample were 100 female buffalo. Collecting data using interview, observation, and literature study methods and analyzing descriptively. The data that has been obtained is then calculated into percentages, averages, and standard deviations, then analyzed descriptively. Buffalo farmers are rice farmers who are still productive with a dominant age of less than 65 years. The main feed given was rice straw, and 64% of buffalo received additional field grass when grazing. The farming experience of farmers was quite long, which is more than 15 years, and was classified as a small-scale farm with the number of buffalo less than 5 heads. The management system used by buffalo farmers is mostly (90%) semi-intensive. The values of gestation length, postpartum estrus, and postpartum estrus were 308.0±7.4 days, 102.2±6.2 days, and 406.8±8.9 days, respectively. The age of first calving for buffalo in the study in Boyolali Regency was 3.60 ± 0.3 years. This study concluded that the reproductive performance of buffaloes in smallholder farms in Boyolali Regency, Central Java Province was in good condition